North-East migrants: Relationships between borderlands and heartlands in a globalising era - Arya, Narendra Kumar (2016)
Globalisation not only shook the socio-eco-cultural landscape of the globe but also ushered in simultaneous unprecedented changes in the fabric and conscience of our nation. The North-East region of India has gradually but steadily emerged as an active participant in the processes and is undergoing many paradigmatic transformations. One of them that we have seen in the recent two decades is substantial spurt in migration from the North-East to several metropolises of the nation. The socio-economic profile of the migrants signifies the vast probabilities for using them to be potent forces of nation-building process in the region, the issue unexplored so far. The goal of nation-building becomes challenging in wake of divergent religious, cultural, linguistic and regional distinctions along with strong desire and constitutional vision of a democratic, secular and socially just society demonstrating the highest levels of inclusiveness and socio-political integrity. This article is an attempt to analyse this purported hypothesis that migrant intellectual class of the region can facilitate this process, if exposed to right political socialisation and attitudinal reinforcement. - Reproduced.
Keywords: Migrants - India, North East; Migrants